2001
DOI: 10.1074/jbc.m006052200
|View full text |Cite
|
Sign up to set email alerts
|

NF-Y Mediates the Transcriptional Inhibition of thecyclin B1, cyclin B2, and cdc25CPromoters upon Induced G2 Arrest

Abstract: During normal cell cycles, the function of mitotic cyclin-cdk1 complexes, as well as of cdc25C phosphatase, is required for G 2 phase progression. Accordingly, the G 2 arrest induced by DNA damage is associated with a down-regulation of mitotic cyclins, cdk1, and cdc25C phosphatase expression. We found that the promoter activity of these genes is repressed in the G 2 arrest induced by DNA damage. We asked whether the CCAATbinding NF-Y modulates mitotic cyclins, cdk1, and cdc25C gene transcription during this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
164
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(179 citation statements)
references
References 59 publications
13
164
1
1
Order By: Relevance
“…wtp53-carrying C2C12 myoblasts (C2-LX) and their dnp53-expressing counterparts (C2-DD) were treated with ADR at the inhibitory concentration 50 (IC 50 ). As previously observed 15 (Figure 1a), this dose promoted an accumulation of the control C2-LX cells in both G1 and G2 phases of the cell cycle within 12-18 h without induction of apoptosis (o3% of TUNEL-positive cells in untreated and treated populations). In contrast, the same treatment induced a massive accumulation of C2-DD cells in the G2/M phase (Figure 1a), which is due to cell cycle progression through mitosis and acquisition of a micronucleated phenotype.…”
Section: Erk2 Is Downregulated Upon Dna Damage Through a P53-mediatedsupporting
confidence: 85%
See 1 more Smart Citation
“…wtp53-carrying C2C12 myoblasts (C2-LX) and their dnp53-expressing counterparts (C2-DD) were treated with ADR at the inhibitory concentration 50 (IC 50 ). As previously observed 15 (Figure 1a), this dose promoted an accumulation of the control C2-LX cells in both G1 and G2 phases of the cell cycle within 12-18 h without induction of apoptosis (o3% of TUNEL-positive cells in untreated and treated populations). In contrast, the same treatment induced a massive accumulation of C2-DD cells in the G2/M phase (Figure 1a), which is due to cell cycle progression through mitosis and acquisition of a micronucleated phenotype.…”
Section: Erk2 Is Downregulated Upon Dna Damage Through a P53-mediatedsupporting
confidence: 85%
“…In contrast, the same treatment induced a massive accumulation of C2-DD cells in the G2/M phase (Figure 1a), which is due to cell cycle progression through mitosis and acquisition of a micronucleated phenotype. 15 When a time-course analysis of p53 and ERK2 expression was performed, increased levels of phosphorylated ERK2 in C2-LX cells were found early after treatment (Figure 1b), as previously observed. 8 However, at later time points, the levels of ERK2 protein and phosphorylation drastically decreased in the C2-LX cells (compare time point 12 and 14 h to 9 h in Figure 1b).…”
Section: Erk2 Is Downregulated Upon Dna Damage Through a P53-mediatedsupporting
confidence: 83%
“…Most repressed genes do not have p53-consensus site in their promoters. For the cdk1 and cdc25C promoters we and others have shown that p53-dependent repression can be mediated through CCAAT-boxes [7,9,10]. Lö hr et al implicated induction of p21 WAF1/CIP1 in the transcriptional downregulation by p53 [11].…”
Section: Introductionmentioning
confidence: 86%
“…One prominent example of a transactivated target gene is the cdk inhibitor p21 WAF1/CIP1 [6]. Other target genes such as several regulators of the G 2 /M checkpoint like cyclin B, cdc25C and cdk1 are repressed by p53 [7][8][9][10]. Many investigations concentrated on solving the mechanism of the p53-dependent repression without identifying one mechanism which would yield a general explanation for the regulatory details.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the tumor suppressor protein p53 plays an important role in reducing the concentration of active Cyclin B/Cdk1 complex in the nucleus contributing to G 2 arrest. To this end, p53 can repress transcription of Cyclin B1, Cyclin B2 and Cdc25C genes (Krause et al, 2000Manni et al, 2001). Additionally, it has been shown that transcriptional repression by p53 is important for the promotion of apoptosis (Ho and Benchimol, 2003).…”
mentioning
confidence: 99%